2010
DOI: 10.3310/hta14540
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effectiveness and cost-effectiveness of stem cell transplantation in the management of acute leukaemia: a systematic review

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below). Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents. Non-UK purchasers will have to pay a small fee for post and packing. For Eur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 118 publications
(295 reference statements)
1
25
0
3
Order By: Relevance
“…Los resultados no contradicen los de otros estudios de costo-efectividad en los que se ha evaluado el trasplante en la consolidación de leucemias agudas en población adulta (11,26,27) mediante árboles de decisión con condiciones agudas como resultado y las mismas distribuciones de probabilidad teóricas.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Los resultados no contradicen los de otros estudios de costo-efectividad en los que se ha evaluado el trasplante en la consolidación de leucemias agudas en población adulta (11,26,27) mediante árboles de decisión con condiciones agudas como resultado y las mismas distribuciones de probabilidad teóricas.…”
Section: Discussionunclassified
“…No existen modelos económicos que comparen el costo-efectividad del trasplante y de la quimioterapia en el tratamiento de la leucemia mieloide aguda en niños (11). Debido a las diferencias en la efectividad y el costo que las alternativas de tratamiento de consolidación para la leucemia mieloide aguda representan para el sistema de salud, es necesario evaluar su costo-efectividad.…”
unclassified
“…[17][18][19][20][21] The economic aspects of HSCT with its patient-centered approach have traditionally concentrated on costs of the individual procedure for an individual patient. 17,[22][23][24] Studies on macro-economic aspects or on cost-effectiveness in individual countries have gained broader acceptance only recently. 11,21,22,25 They were triggered in part by some rapid changes in the use of HSCT, such as for breast cancer or chronic myeloid leukemia 18,26 and by the rising awareness of the disturbing gap between unlimited requests and limited resources in any health care system.…”
Section: Discussionmentioning
confidence: 99%
“…Four systematic reviews evaluated the effect of autologous hematopoietic cell transplantation (HCT) in first CR (Ashfaq, et al 2010, Levi, et al 2004, Nathan, et al 2004, Wang, et al 2010.…”
Section: Autologous Hematopoietic Cell Transplantationmentioning
confidence: 99%
“…Eight reviews and meta-analyses were identified but only three of them were systematic and comprehensive (Ashfaq, et al 2010, Hubel, et al 2011, Koreth, et al 2009. Koreth et al performed a systematic review comparing allogeneic HCT with conventional consolidation chemotherapy or autologous HCT (Koreth, et al 2009).…”
Section: Allogeneic Hematopoietic Cell Transplantationmentioning
confidence: 99%